2015
DOI: 10.1128/jcm.00567-15
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Sample Preparation Methods, Instrumentation Platforms, and Contemporary Commercial Databases for Identification of Clinically Relevant Mycobacteria by Matrix-Assisted Laser Desorption Ionization–Time of Flight Mass Spectrometry

Abstract: When mycobacteria are recovered in clinical specimens, timely species-level identification is required to establish the clinical significance of the isolate and facilitate optimization of antimicrobial therapy. Matrix-assisted laser desorption ionization-time of flight mass spectrometry (MALDI-TOF MS) has recently been reported to be a reliable and expedited method for identification of mycobacteria, although various specimen preparation techniques and databases for analysis are reported across studies. Here w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
43
1

Year Published

2016
2016
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(46 citation statements)
references
References 17 publications
2
43
1
Order By: Relevance
“…As it allows pathogen-specific culture and protein extraction protocols (34,35), we first optimized our in-house mycobacterial cell disruption and protein extraction protocol for MALDI-TOF MS analysis. Upon comparison of various described protocols using M. tuberculosis H37Rv cells (22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34), we found that in our hands, bead beating in the presence of 1.2 ml of 70% ethanol gave the best output in terms of peak intensity and identification scores (Table S1).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…As it allows pathogen-specific culture and protein extraction protocols (34,35), we first optimized our in-house mycobacterial cell disruption and protein extraction protocol for MALDI-TOF MS analysis. Upon comparison of various described protocols using M. tuberculosis H37Rv cells (22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34), we found that in our hands, bead beating in the presence of 1.2 ml of 70% ethanol gave the best output in terms of peak intensity and identification scores (Table S1).…”
Section: Resultsmentioning
confidence: 99%
“…Unlike most bacteria, mycobacteria require prior inactivation and disruption of the mycolic acid-rich cell wall, both for biosafety reasons and to liberate the cellular protein content. Numerous suitable procedures have been proposed, combining heat-killing, ethanol, sonication, and/or silica-based bead beating preceding the regular formic acid/acetonitrile extraction (21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33). The reported success rates vary between 55% and 98% correct species-level identifications, but the large variety in strain collections, culture conditions, extraction protocols, hardware, and databases hinder data comparison between publications.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Matrix-assisted laser desorption ionization-time of flight mass spectrometry (MALDI-TOF MS) has been utilized in the clinical microbiology laboratory for rapid and accurate identification of bacteria, mycobacteria, and yeasts (2)(3)(4)(5)(6)(7)(8)(9). For filamentous fungi, databases have been limited, and unlike bacteria, filamentous fungi require additional processing steps to disrupt the cell wall, extract proteins, and inactivate the isolate (10).…”
mentioning
confidence: 99%
“…Several laboratories have previously published descriptions of the use of this standard for the identification of Mycobacterium spp. (11,12). Further supplementation of existing libraries will be necessary to improve the identification of select species.…”
mentioning
confidence: 99%